2021
DOI: 10.21037/jgo-21-403
|View full text |Cite
|
Sign up to set email alerts
|

Expression, clinical significance and correlation of RUNX3 and HER2 in colorectal cancer

Abstract: Background: The incidence of colorectal cancer is high and on the rise. The genetic and protein expressions of RUNT-associated transcription factor 3 (RUNX3) and human epidermal growth factor receptor 2 (HER2) in colorectal cancer (CRC) and adjacent normal tissues were detected to preliminarily explore their correlation and clinical significance.Methods: CRC specimens excised during general surgery were selected for localization and quantitative analysis of protein and gene expression by SP (Streptavidin-perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Investigations in colorectal cancer confirmed that a decline in RUNX3 expression correlates with increased cell proliferation and invasion [ 94 ]. This was further corroborated by Wu et al, who detected a marked downregulation of RUNX3 in colorectal cancer, concomitant with an inverse correlation with HER2 expression [ 95 ]. Cumulatively, these findings underscore RUNX3's predominant function as a tumor suppressor, consistently found to be downregulated in diverse cancer types.…”
Section: Runx Proteins In the Landscape Of Cancer Expressionsupporting
confidence: 56%
“…Investigations in colorectal cancer confirmed that a decline in RUNX3 expression correlates with increased cell proliferation and invasion [ 94 ]. This was further corroborated by Wu et al, who detected a marked downregulation of RUNX3 in colorectal cancer, concomitant with an inverse correlation with HER2 expression [ 95 ]. Cumulatively, these findings underscore RUNX3's predominant function as a tumor suppressor, consistently found to be downregulated in diverse cancer types.…”
Section: Runx Proteins In the Landscape Of Cancer Expressionsupporting
confidence: 56%
“…On the other hand, there are also plenty of reports of TFs acting as tumor suppressors in CRC; among them is FOXO3, whose downregulation correlates with a better prognosis in CRC patients [76,77]. Another example is RUNX3-this TF is a target of the TGF-β pathway and is downregulated in CRC patient samples [78]. It has been reported that RUNX3 can induce apoptosis [79] and inhibit metastasis and angiogenesis [80].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 has been shown to regulate RUNX3 expression ( 13 ). Based on results reported in our previous work ( 14 16 ), we aimed to investigate whether RUNX3 and EZH2 can evaluate the clinical efficacy of neoadjuvant therapy and prognosis of LARC.…”
Section: Introductionmentioning
confidence: 99%